KATA-KATA UMPATAN DALAM FILM WHY HIM? DISUTRADARAI OLEH JOHN HAMBERG - KAENG, TISA SARA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT Language is the most important part for humans to interact with other humans or any other living things. This research is entitled â€œSwear Words in the Movie Why Him? Directed by John Hamburgâ€. The aims of this research are to identify and analyze the data and also to find the meaning of them. The theories used in this research are Pinker (2007) and Urban Dictionary to analyze the types and meaning of the data. The data are the swear words in the movie Why Him? Directed by John Hamberg. The obtained data in this research were analyzed by using descriptive analysis. There are 142 total data in the movie and there are 54 data in the classification. The result of this research shows The 5 types of swear words in the theory of Pinker, which are Dysphemistic Swearing, Abusive Swearing, Emphatic Swearing, Idiomatic Swearing and Cathartic Swearing are found in this research. There are 46 different swear words in the movie and by using the Urban Dictionary, the meaning of them are related to sex, body parts, taboo words in religion, excrement, family origin, mental illness, profession and animal.Â  Â Keywords: Swear words, film Why Him?, Descriptive Analysis